Towards systemic evaluation in turbulent times – Second-order practice shift. (April 2020) - Schmidt-Abbey, Barbara; Reynolds, Martin; Ison, Ray
The need for, and possibilities of, a second-order shift in evaluation practice are explored. Second-order evaluation practice enables an evaluator to improve practice as a skilled practitioner, acknowledging her embeddedness within an evaluand. The article explores evaluation practice as experienced by professional evaluators, using ideas from developmental evaluation coupled with systemic evaluation in the tradition of systems thinking in practice. Systemic evaluation aims to capture systemic sensibilities – the bigger picture – of complex turbulent situations of change underpinning evaluands. Attributes of second-order practice with systemic evaluation are understood as being aligned with both systemic and systematic modes of evaluation praxis. Personal experiences are provided where this juxtaposing praxis has been found wanting. By example, a systems thinking in practice framework is explored as heuristic support for making a second-order practice shift. The article concludes with a discussion of some implications for developments in professionalising evaluation practice and research.